Inhalation Exposure to PM2.5 Counteracts Hepatic Steatosis in Mice Fed High-fat Diet by Stimulating Hepatic Autophagy. Issue 1 (December 2017) - Qiu, Yining; Zheng, Ze; Kim, Hyunbae; Yang, Zhao; Zhang, Gary; Shi, Xiangyang; Sun, Fei; Peng, Changya; Ding, Yuchuan; Wang, Aixia; Chen, Lung-Chi; Rajagopalan, Sanjay; et al.
Abstract Air pollution is associated with the increased risk of metabolic syndrome. In this study, we performed inhalation exposure of mice fed normal chow or a high-fat diet to airborne fine particulate matters (PM2.5 ), and then investigated the complex effects and mechanisms of inhalation exposure to PM2.5 on hepatic steatosis, a precursor or manifestation of metabolic syndrome. Our studies demonstrated that inhalation exposure of mice fed normal chow to concentrated ambient PM2.5 repressed hepatic transcriptional regulators involved in fatty acid oxidation and lipolysis, and thus promoted hepatic steatosis. However, PM2.5 exposure relieved hepatic steatosis in high-fat diet-induced obese mice. Further investigation revealed that inhalation exposure to PM2.5 induced hepatic autophagy in mouse livers in a manner depending on the MyD88-mediated inflammatory pathway. The counteractive effect of PM2.5 exposure on high-fat diet-induced hepatic steatosis was mediated through PM2.5 -induced hepatic autophagy. The findings from this study not only defined the effects and mechanisms of PM2.5 exposure in metabolic disorders, but also revealed the pleotrophic acts of an environmental stressor in a complex stress system relevant to public health.